Procollagen C-Proteinase Enhancer-1 (PCPE-1) deficiency in mice reduces liver fibrosis but not NASH progression - Sansilvestri Morel, Patricia; Duvivier, Valerie; Bertin, Florence; Provost, Nicolas; Hammoutene, Adel; Hubert, Edwige-Ludiwyne; Gonzalez, Arantxa; Tupinon-Mathieu, Isabelle; Paradis, Valerie; Delerive, Philippe (PLOS ONE, 2022)
Background and aims Nonalcoholic Steatohepatitis (NASH) is a major cause of end-stage liver diseases such as cirrhosis and hepatocellular carcinoma resulting ultimately in increased liver-related mortality. Fibrosis is the main driver of mortality in NASH. Procollagen C-Proteinase Enhancer-1 (PCPE-1) plays a key role in procollagen maturation and collagen fibril formation. To assess its role in liver fibrosis and NASH progression, knock-out mice were evaluated in a dietary NASH model. Methods Global constitutive Pcolce-/- and WT male mice were fed with a Choline Deficient Amino acid defined High Fat Diet (CDA HFD) for 8 weeks. Liver triglycerides, steatosis, inflammation and fibrosis were assessed at histological, biochemical and gene expression levels. In addition, human liver samples from control and NASH patients were used to evaluate the expression of PCPE-1 at both mRNA and protein levels. Results Pcolce gene deficiency prevented diet-induced liver enlargement but not liver dysfunction. Furthermore, liver triglycerides, steatosis and inflammation were not modified in Pcolce-/- male mice compared to WT under CDA HFD. However, a significant decrease in liver fibrosis was observed in Pcolce-/- mice compared to WT under NASH diet, associated with a decrease in total and insoluble collagen content without any significant modifications in the expression of genes involved in fibrosis and extracellular matrix remodeling. Finally, PCPE-1 protein expression was increased in cirrhotic liver samples from both NASH and Hepatitis C patients. Conclusions Pcolce deficiency limits fibrosis but not NASH progression in CDA HFD fed mice.